2022
DOI: 10.20964/2022.09.42
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Zn-Ca Phosphate Coating in Presence of PTFE on 45 Steel and its Corrosion Properties in Simulated Seawater

Abstract: Zn-Ca phosphate coating in presence of PTFE was prepared on the surface of 45 steel by dipping method using a phosphate solution containing PTFE particles. By investigating the influence of the amount of PTFE particles added, stirring rate, phosphate solution temperature and phosphate time on the thickness and PTFE particles content of Zn-Ca phosphate coating in presence of PTFE , the optimal process parameters for preparing Zn-Ca phosphate coating in presence of PTFE were determined as follows: amount of PTFE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Similarly, the effects of different phosphate solution temperatures and phosphate time immersions on the Zn-Ca phosphate coating with PTFE on the surface of 45 steel were studied by Zhang et al through the dipping method. It was concluded that the optimum conditions for coating thickness and PTFE particle content were achieved at a phosphate solution temperature of 65 • C. The elevated temperature accelerates hydrolysis and crystallization reactions, increasing the coating formation rate and improving coating thickness [13].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the effects of different phosphate solution temperatures and phosphate time immersions on the Zn-Ca phosphate coating with PTFE on the surface of 45 steel were studied by Zhang et al through the dipping method. It was concluded that the optimum conditions for coating thickness and PTFE particle content were achieved at a phosphate solution temperature of 65 • C. The elevated temperature accelerates hydrolysis and crystallization reactions, increasing the coating formation rate and improving coating thickness [13].…”
Section: Introductionmentioning
confidence: 99%